DETERMINANTS OF SUBJECTIVE WELLBEING: LITHUANIAN CASE - Dirzyte, Aiste; Patapas, Aleksandras (European Scientific Journal, ESJ, 2015)
This paper presents some selected results of the survey (representative sample, n=1002) which was conducted in Lithuania in 2014. This research was funded by the European Social Fund under the Global Grant measure (No. VP1-3.1-Å MM-07-K-03-032). The study revealed various relations between Lithuaniansâ€™ wellbeing, attitudes towards life, emotional states, and suicidal ideation. The results demonstrated statistically significant negative relationship between Lithuaniansâ€™ satisfaction with life and negative emotional states: anxiety, psychological pain, sadness, hopelessness, helplessness, meaninglessness. It was found statistically significant positive relationship between Lithuaniansâ€™ satisfaction with life and positive emotional states: joy, gratefulness, enthusiasm, trust, confidence, compassion, hopefulness, happiness, peacefulness. The results have also demonstrated positive correlations between satisfaction with life and positive life perceptions: clear goals in life, perceiving life as fulfilled, worthy living, pleasant, meaningful. The results might imply that in order to diminish the rates of suicides in Lithuania, there is a need to implement evidence based psycho-educational programs and interventions.